Encoding strategy mediates the effect of electrical stimulation over posterior parietal cortex on visual short-term memory. (July 2020) - Wang, Sisi; Itthipuripat, Sirawaj; Ku, Yixuan
Abstract: Over past decades, converging neuroimaging and electrophysiological findings have suggested a crucial role of posterior parietal cortex (PPC) in supporting the storage capacity of visual short-term memory (VSTM). Moreover, a few recent studies have shown that electrical stimulation over PPC can enhance VSTM capacity, making it a promising method for improving VSTM function. However, the reliability of these results is still in question because null findings have also been observed. Among studies that reported significant effects, some found increased VSTM capacity only in people with low capacity. Here, we hypothesized that subjects' encoding strategy might be a key source of these variable results. To directly test this hypothesis, we stimulated PPC using transcranial direct-current stimulation (tDCS) in male and female human subjects instructed to employ different encoding strategies during a VSTM recall task. We found that VSTM capacity was higher in subjects who were instructed to remember all items in the supra-capacity array of visual stimuli (i.e., the remember-all group), compared to subjects who were told to focus on a subset of these stimuli (i.e., the remember-subset group). As predicted, anodal tDCS over PPC significantly enhanced VSTM capacity only in the remember-subset group, but not in the remember-all group. Additionally, no effect of encoding strategy or its interaction with electrical stimulation was found on VSTM precision. Together, these results suggest that encoding strategy has a selective influence on VSTM capacity and this influence of encoding strategy mediates the effect of electrical stimulation over PPC on VSTM function.